Digital colonialism: South Africa's education transformation in the shadow of Silicon Valley - Kwet, Michael (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This dissertation investigates the social implications of technology choices for the emerging education transformation of the South African basic education sector. In October 2015, then President Jacob Zuma launched Operation Phakisa Education (OPE), an initiative designed behind closed doors to fast-track digital education into all South African public schools. This study identifies and analyses policy choices and perspectives regarding the technology considered and deployed for the national education rollout. It documents the OPE proposal, and examines how e-education policy choices relate to humanitarian objectives. Theoretically, this study draws upon libertarian socialist theory (anarchism) to examine the sociology of education technology policy. Using anarchist theory, it assesses the perspective, aims, and choices of e-education policy at the national level. It also draws on the Free Software philosophy for society as articulated by Richard Stallman and Eben Moglen. Finally, it compares classic colonialism with global power in the digital era, and posits a theory of digital colonialism. Synthesizing anarchism and the Free Software philosophy into a single theoretical framework "“ placed into the context of colonial relations "“ it is the first work to apply anarchist sociological theory to education technology policy, and the first doctoral study on digital colonialism. For its methodology, this dissertation utilizes two qualitative methods: document analysis and semi-structured interviews. Interview subjects include high-level e-education policymakers and administrators in government, key stakeholders, and experts at the intersection of technology innovation and human rights. These methods were used to both identify and interrogate e-education policy as it relates to the humanitarian objectives of education policy at the national level. The findings demonstrate that South African education policy is beholden to largely United States-based corporations and models for e-education. The study found that the types of technologies for consideration in education are rooted in surveillance capitalism, which is spreading across the world. It contends that current e-education policy choices will entrench the power and exploitation of US state-corporate power in South African education, economy, and society. It argues that an alternative set of choices, People's Technology for People's Power, is consistent with the spirit of South African technology policy, and should be chosen for South African schools in order to counter the power of foreign power and resist surveillance capitalism. This dissertation is the first publication to document and analyze what the new government education policy is about and how it relates to equality and human rights. It argues that present South African e-education policy constitutes a new form of digitally-driven technocratic neoliberalism which ultimately favors ruling class interests in the United States and South Africa. It also argues that OPE violates South Africa's Free and Open Source policy and the spirit of democracy outlined in the Phakisa methodology and the Batho Pele principles. This study found that OPE replicates the latest trends in e-education implementation popular in Silicon Valley. Tech multinationals are providing both the products and models for use in South Africa. The dissertation concludes that US technological and conceptual dominance in South African education constitutes digital colonialism. It emphasizes the need for public inclusion in the policy process, and proposes alternative policies and technologies for e-education based on the idea of People's Technology for People's Power. It also argues that current scholarship on education technology neglects the political and sociological importance of People's Technology to education, economy, and society, as well as the global significance of Big Tech dominance vis-a-vis digital colonialism, and that subsequent literature would be enriched by addressing these issues.
Keywords: Operation Phakisa Education (South Africa); Educational technology -- South Africa; Internet in education -- South Africa; Educational sociology -- South Africa; Technological innovations -- South Africa; Technological literacy -- South Africa; Education and state -- South Africa; Open source software -- South Africa; Electronic surveillance -- Social aspects -- South Africa; Privacy, Right of -- South Africa; Business and education -- South Africa